Is the current comprehensive view to the human being, enough? - Ricardo Ángel González Menéndez (Medisur)
Quantity and quality assessment with which the different components on the natural, cultural and social environment achieve to satisfy the range of needs of human beings during the interaction with the environment results of vital importance to understand its comprehensive development. Man has biologic, psychological, social, cultural and cultural needs which should be satisfied for its full development. This paper reflects on the current imperative to form individuals with a developed spirituality, as the only alternative facing hyperhedonism and passivity that has invaded the world today.